2021
DOI: 10.1177/1420326x20979274
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution and health risk assessment in Northeastern China: A case study of Jilin Province

Abstract: In recent years, the pollution of the air environment has been increasing, which has seriously endangered human health. The large amount of coal burning and automobile exhaust emissions in winter have caused serious regional pollution, which has greatly increased the prevalence of respiratory disease of people. The purpose of this study is to use Jilin Province as an example to map out the environmental pollution status in Northeastern China, and to provide suggestions for the improvement of the atmospheric en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…With low combustion efficiency, emissions of CO, PM 2.5 , black carbon (BC) and PAHs have a significant adverse impact on the indoor and ambient air quality. 36 Other research 37 confirmed that coal burning and automobile exhaust emissions caused serious regional pollution in winter, which greatly increased the prevalence of respiratory diseases. The government should strive to promote technologies and measures to improve the utilization of biomass energy.…”
Section: Resultsmentioning
confidence: 96%
“…With low combustion efficiency, emissions of CO, PM 2.5 , black carbon (BC) and PAHs have a significant adverse impact on the indoor and ambient air quality. 36 Other research 37 confirmed that coal burning and automobile exhaust emissions caused serious regional pollution in winter, which greatly increased the prevalence of respiratory diseases. The government should strive to promote technologies and measures to improve the utilization of biomass energy.…”
Section: Resultsmentioning
confidence: 96%
“…Particulate matter (PM), as an important pollutant in indoor air, has been a wide concern for many years. [3][4][5] The harm posed by PM is not limited by its own existence, 6 but also due to the attachment of heavy metals and polycyclic aromatic hydrocarbons (PAHs) and other harmful substances to its loose and porous structure. 7 Indoor PMs with different sizes can enter the human body in different ways.…”
Section: Introductionmentioning
confidence: 99%
“…Particulates tend to reach deep into the body and have a negative impact on health. Relevant studies have shown that high levels of particulates exposure increase cardiovascular risk [2][3][4][5][6], respiratory disease [7][8][9][10], premature death [11][12][13], etc. The chemical substances contained in particulates, such as polycyclic aromatic hydrocarbons (PAHs) and heavy metals, pose a more serious health risk than particulates only [14,15].…”
Section: Introductionmentioning
confidence: 99%